Posthumanism and the Science Fiction of Philip K. Dick Has the Future he Prophesied Arrived? - BELKHARCHOUCHE, Malika (Journal of Human Sciences, 2023)
The aim of this study is to investigate the human condition transmuted by science and technology as depicted in the works of the American science-fiction writer Philip K. Dick and its relevance to the contemporary state of humanity and the concept of posthumanism. The paper explores first the notion of posthumanism as a cultural and philosophical framework for the 21st century that describes the advent of a new epoch of transformed humanity by the excessive dependence on technology. Then Philip K. Dick, whose most acclaimed works were written during the 1960s and 1970s, is introduced as the visionary writer who had an unusual discernment of the future of the world and the cost humans have paid for the unlimited uses of technology in every area of human life and activity. Through the analysis of two of his major novels, Do Androids Dream of Electric Sheep? and Ubik, I intend to answer the pertinent question as to whether the state of humanity Philip Dick portrays in his works corresponds with the reality of today’s world and the notion of posthumanity; in other words, has the future of humanity Philip Dick predicted in his fiction arrived?